The Rights of the Child forgotten in Italy’s coronavirus emergency - Tolomelli, Alessandro (Comparative Cultural Studies: European and Latin American Perspectives, 2020)
The coronavirus emergency radically changes our habits and way of life, and clearly highlight the inadequacy of our decision-making apparatus and the latent injustices in society. The paper focuses on the failure consideration of the needs and rights of the Child in the urgent decrees implemented by the Italian Government and by the most affected Regions of the peninsula. In a general context in which the perception of the danger activates regressive mechanisms at a social level (such as the search for the scapegoat and the polarization of the behaviours of the citizens), one would expect that the ruling classes maintain rationality and foresight in management of the crisis. Moreover, a scarce “widespread pedagogical culture” which generated the complete removal of the child and educational issue from the political agenda and from public discourse up to the present day. The question of the relationship between education and democracy and the education as a community task must be reconsider as a prior topic for our society, as John Dewey taught.